2003
DOI: 10.1128/jcm.41.8.3584-3591.2003
|View full text |Cite|
|
Sign up to set email alerts
|

Genotyping and Phenotyping of Beta2-Toxigenic Clostridium perfringens Fecal Isolates Associated with Gastrointestinal Diseases in Piglets

Abstract: Although Clostridium perfringens is recognized as an important cause of clostridial enteric diseases, only limited knowledge exists concerning the association of particular C. perfringens toxinotypes (type A to E) with gastrointestinal (GI) diseases in domestic animals. Some C. perfringens isolates also produce the newly discovered beta2-toxin (CPB2). Recent epidemiological studies suggested that C. perfringens isolates carrying the gene encoding CPB2 (cpb2) are strongly associated with clostridial GI diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
100
0
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(111 citation statements)
references
References 24 publications
(39 reference statements)
4
100
0
6
Order By: Relevance
“…Recently, the newly discovered beta 2 toxin has been associated with porcine, equine and bovine gastro-enteritis Bacciarini et al, 2003;Waters et al, 2003). This toxin has also been demonstrated in avian C. perfringens type A strains , but its exact role in pathogenesis needs to be further elucidated.…”
Section: Perfringens Virulence Factorsmentioning
confidence: 99%
“…Recently, the newly discovered beta 2 toxin has been associated with porcine, equine and bovine gastro-enteritis Bacciarini et al, 2003;Waters et al, 2003). This toxin has also been demonstrated in avian C. perfringens type A strains , but its exact role in pathogenesis needs to be further elucidated.…”
Section: Perfringens Virulence Factorsmentioning
confidence: 99%
“…Beta2 toxin, encoded by cpb2, which is another toxin produced by many C. perfringens isolates (Gibert et al, 1997), has been associated with NE in horses (Bacciarini et al, 2003), ruminants (Lebrun et al, 2007), and pigs Waters et al, 2003). However, it has been suggested that beta2 toxin is not involved in NE in poultry (Gholamiandekhordi et al, 2006;Crespo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For many years it has been thought that the lethal properties of type A strains, is determined by the amount of α toxin produced (15). However, the last two decades has brought new data in the field, confirming the participation of additional toxins (netB and β2 toxin) in the pathogenesis of enteritis caused by C. perfringens type A in various species of animals (4,5,7,9,18). Bearing in mind that the confirmation of the presence of the gene encoding the bacterial toxin does not mean the production of the toxin, the aim of the study was to assess the presence and expression of toxin genes of C. perfringens strains isolated from healthy pigs.…”
mentioning
confidence: 99%